Association of academic stress & performance in continuous assessment among pharmacy students in body system course - Soe , May Khin; Baharudin, Mohamad Sharul Fahmi (IIUM Medical Journal Malaysia, 2016)
Introduction: Undergraduate Pharmacy students find the program is stressful. This study compares the perceived stress score (PSS) of third year Pharmacy students and their performance via continuous assessment (CAM) in a body system course. Methods: The relationship between the PSS and their academic performance, though out the semester were explored for 114 students including 25 male and 85 female. In this cross-sectional study, questionnaires were distributed to assess their PSS, other relevant questions and the result in four quizzes on the course were recorded periodically and analyzed descriptively. Results: The mean value of the whole class PSS score was found (38.66 ± 6.46). Females’ PSS in 1st quiz was 38.76 ± 5.56 and male’s was 39.21 ± 5.48 and quiz 2 for female was 38.61 ± 6.27 whereas 40.1 ± 7.48 in male. That value in quiz 3 and 4 for female was 38.10 ± 7.18 and male was 39.69± 8.68. However, there is no significant difference in gender. The PSS score for all participants was found highest in the second quiz (38.99 ± 6.60) whereas the mean marks they obtained were lowest (4.97 ± 1.36) compared to other quizzes but their relation is weakly significant. Total scoring of the CAM for the whole class was found even lower compared to previous batches, 23.83 ± 3.88. They were engaged with various co-curriculum activities and complained of not having enough time to study and revise. The unsatisfactory performance might be due to heavy topics and time constraint. Conclusions: Stress and time management are critical elements for undergraduate students to perform well academically regardless of their stress level.